Ruqyah Air dalam Kegiatan Tasmi’ bi Al-Ghaib: Kajian Living Qur’an pada Ma’had Daarut Tahfiz Al-Ikhlas Aceh - Samsul Bahri; Minnatul Maula (TAFSE: Journal of Qur'anic Studies, 2022)
One of the functions of the Qur'an is as a shifa' (medicine) as Allah says in Sura al-Isra' verse 82. There are various ways applied to obtain the function of syifa', one of which is to consume water that has been recited verses of the Qur'an. This paper will discuss the function of the Qur'an as shifa', shahadah tahfiz through tasmi' bil ghaib activities and the use of water ruqyah in tasmi' bil ghaib activities. This study is a combination of literature and field research conducted in Ma'had Daarut Tahfiz Al-Ikhlas. Data were collected by observation, interview, and documentation techniques. Furthermore, data analysis is carried out with qualitative descriptive techniques. The results showed that the Qur'an can be a cure for physical and spiritual diseases through the therapy of reading verses from the Qur'an which is also accompanied by the practice of zikir and worship to draw closer to Allah. Shahadah tahfiz al-Qur'an in Ma'had Daarut Tahfiz Al-Ikhlas as a form of living Qur'an that is carried out by tasmi' bil ghaib, namely by witnessing and listening to the memorization of the Qur'an of 30 juzs by the students in front of the crowd. Tasmi' bil ghaib activities were followed by the procurement of rugyah of water which was used by students, student’s parents and the community as a shifa'. The ruqyah of water is believed to be a cause of positive energy for anyone who consumes it. Salah satu fungsi al-Qur’an adalah sebagai syifa’ (obat) sebagaimana firman Allah dalam Surat al-Isra’ ayat 82. Terdapat berbagai cara yang diterapkan untuk mendapatkan fungsi syifa’ tersebut, salah satunya adalah dengan mengonsumsi air yang telah dibacakan ayat Al-Qur’an. Tulisan ini akan mendiskusikan tentang fungsi al-Qur’an sebagai syifa’, syahadah tahfiz melalui kegiatan tasmi’ bil ghaib dan pemanfaatan ruqyah air dalam kegiatan tasmi’ bil ghaib. Kajian ini merupakan gabungan dari penelitian kepustakaan dan lapangan yang dilakukan di Ma’had Daarut Tahfiz Al-Ikhlas. Data dikumpulkan dengan teknik observasi, wawancara, dan dokumentasi. Selanjutnya analisis data dilakukan dengan teknik deskriptif kualitatif.  Hasil penelitian menunjukkan bahwa al-Qur’an dapat menjadi obat bagi penyakit jasmani maupun ruhani melalui terapi pembacaan ayat al-Qur’an yang juga disertai pengamalan zikir dan ibadah untuk mendekatkan diri kepada Allah. Syahadah tahfiz al-Qur’an di Ma’had Daarut Tahfiz Al-Ikhlas sebagai bentuk dari living al-Qur’an yang dilaksanakan secara tasmi’ bil ghaib yaitu dengan mempersaksikan dan memperdengarkan hafalan al-Qur’an 30 juz para santri di hadapan orang banyak. Kegiatan tasmi’ bil ghaib diikuti dengan pengadaan ruqyah air yang dimanfaatkan santri, wali santri maupun masyarakat sebagai syifa’. Air ruqyah tersebut diyakini mampu menjadi sebab yang menimbulkan energi positif bagi siapa saja yang mengkonsumsinya.